Trishuli Assessment Tool - Field Manual : A Standardized Methodology for Freshwater Aquatic Biodiversity Sampling and Long-Term Monitoring for Hydropower Projects in the Himalayan Region - International Finance Corporation (Washington, DC, 2022)
The Trishuli Assessment Tool is a standardized methodology for sampling freshwater aquatic biodiversity in hydropower projects. This tool was developed to: 1) strengthen the collection of aquatic biodiversity data for environmental impact assessments (EIAs) and international-level environmental and social impact assessments (ESIAs); and 2) provide a simple yet standardized method for the long-term monitoring of aquatic biodiversity in relation to hydropower projects. The tool was developed by a group of 30 international and Nepalese aquatic scientists at a workshop in 2019 and tested during a field survey in 2020. It provides a field sampling methodology for three focal groups of aquatic biodiversity: fish, macroinvertebrates, and periphyton as indicators of overall aquatic biodiversity. This field manual provides guidance for implementing the Trishuli assessment tool in the rivers of Nepal and other Himalayan regions. The manual is applicable to all types of hydropower projects (HPPs), from small run-of-river to larger peaking projects because all of them have some impact on the aquatic environment.